Losing Hold of the American Dream: A Qualitative Exploration of the Relationship Between Foreclosure and Psychological and Physical Health. (April 2021) - Collins, Cyleste C.; DeRigne, LeaAnne
The purpose of this study was to conduct an exploratory qualitative study of the impact of foreclosure on health. Twenty-nine interviews were conducted with people who had children under the age of 18 years at the time of the foreclosure. Interviews explored perspectives on the foreclosure experience, including factors that led to the foreclosure, the meaning(s) the foreclosure has had for them, and the health care impact. Thematic analyses identified themes underlying families' descriptions of their experiences. Participant families described the stress of losing a home and how that had contributed to a number of psychological and physiological ailments. Psychological effects included high levels of perceived stress, anxiety, grief, and a sense of shame and failure, while physiological effects were often described as either stress-induced or existing issues worsened by stress. These findings are discussed with regard to their implications for improving services and policies offered to families.